KAJIAN MODEL KELEMBAGAAN PERANAN DUNIA USAHA DALAM PENATAAN RUANG - herlin (TEKNOKRIS, 2023)
One of the manifestations of development is the arrangement of areas according to spatial rules to create safe, comfortable, productive and sustainable spaces. As stated in the mandate of Law no. 26 of 2017 concerning Spatial Planning. Space includes land space, ocean, air and space in the earth. Judging from its nature, land is the center of all human activities, land as a strategic element of space is a basic need that concerns the livelihoods of many people. Land and Spatial Planning Policy within the investment framework is directed at efforts to encourage investment by reducing various obstacles, in order to foster competitiveness, it is this challenge that is the background of this study to initiate the need for a forum for the institutional model of Business World Awareness - Spatial Planning. This is intended to be able to carry out communication, consultative, participatory, advocacy in the implementation, utilization, supervision, and evaluation of spatial planning, especially among the business community which often experience problems/conflicts, as an effort to realize development that is productive, just and sustainable, by applying the principles, rules and norms of spatial planning.